2017
DOI: 10.1177/2048872617741733
|View full text |Cite
|
Sign up to set email alerts
|

Association between short and long sleep durations and cardiovascular outcomes: a systematic review and meta-analysis

Abstract: Both short (<7 hours) and long sleep durations (>9 hours) can increase the risk of overall cardiovascular disease mortality, particularly in Asian populations and elderly individuals. Future epidemiological studies would ideally include objective sleep measurements, rather than self-report measures, and all potential confounders, such as genetic variants.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
77
4
3

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 103 publications
(92 citation statements)
references
References 36 publications
0
77
4
3
Order By: Relevance
“…With CVD mortality, we also observed a similar nonsignificant positive association (27% increased CVD mortality) with long sleep. Our findings somewhat disagree with previous studies [ 18 , 22 , 30 , 38 , 39 ] which reported an increased CVD mortality associated with both short and long sleep. As a previous meta-analysis found a positive association with short sleep when specific CVD type (stroke, coronary heart disease) was examined but not when total CVD was examined [ 40 ], the association with short sleep may be specific to certain CVD type.…”
Section: Discussioncontrasting
confidence: 99%
“…With CVD mortality, we also observed a similar nonsignificant positive association (27% increased CVD mortality) with long sleep. Our findings somewhat disagree with previous studies [ 18 , 22 , 30 , 38 , 39 ] which reported an increased CVD mortality associated with both short and long sleep. As a previous meta-analysis found a positive association with short sleep when specific CVD type (stroke, coronary heart disease) was examined but not when total CVD was examined [ 40 ], the association with short sleep may be specific to certain CVD type.…”
Section: Discussioncontrasting
confidence: 99%
“…Wang et al [ 8 ] also did not find an association between anaemia, diabetes, and short and/or long sleep. This study did not confirm findings from previous studies on the association between hypertension, diabetes mellitus, ischemic heart disease, COPD, multimorbidity, and short sleep [ 5 , 6 , 7 , 8 , 9 , 10 ], and the association between hypertension, diabetes, cardiovascular disease, hyperlipidaemia, cerebrovascular diseases, multi-morbidity, and long sleep [ 4 , 8 , 9 , 11 , 12 , 13 ]. The lack of associations found in this study may be attributed to the low prevalence of short sleep and very high prevalence of long sleep.…”
Section: Discussioncontrasting
confidence: 99%
“…Regarding specific chronic conditions, this study only found an association between myocardial infarction and long sleep and in an unadjusted analysis, cataracts and short sleep, while there no associations for anaemia, angina, chronic bronchitis, diabetes, dyslipidaemia, heart failure, hypertension, kidney disease, stroke, HIV, and TB. Various studies have confirmed the relationship between cardiovascular conditions such as myocardial infarction with long sleep [ 4 , 8 , 9 , 10 , 11 , 12 , 13 ]. In a study in Ghana, sleep duration was also not associated with the prevalence of cardiovascular disorders [ 15 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, the evidence supporting this association is not consistent. Some studies have found a link between long or short sleep duration and an increased risk of stroke (6)(7)(8)(9), whereas other studies have claimed no significant association (10,11). These conflicting findings from observational epidemiological studies may be due to differences in the study population, sample size, sleep duration assessment methods, or covariates adjusted in the statistical models.…”
Section: Introductionmentioning
confidence: 98%